Gambaran Tentang Pemberian Imunisasi Dasar Lengkap Pada Balita Di Dusun Tita Mandiri Desa Waisala Tahun 2023 - Epi Dusra; Maryam Lihi (Pusat Riset dan Inovasi Nasional, 2023)
Immunization is an attempt to provide immunity to toddlers by injecting vaccines into the body so that the body makes antibodies to prevent certain diseases. The purpose of this study was to describe the administration of complete basic immunization in Tita Mandiri hamlet, Waisala village. This type of research is quantitative research with a descriptive approach. In this study, the population was mothers who had toddlers totaling 18 people. The sampling technique is to use total sampling where the entire population is used as a sample, namely 18 people. Data analysis used a computerized process which was analyzed univariately and presented in the form of tables and narratives. The results showed that 33.3% of children in the yes category received complete basic immunization and 66.7% did not receive complete basic immunization. It was concluded that there are still babies who have not received complete basic immunization in Tita Mandiri hamlet.